THE IMPACT OF GOVERNMENT SUBSIDIES ON BATTERY SWAPPING MODE: FROM THE PERSPECTIVE OF BATTERY SWAPPING SUPPLY CHAIN - Wang, Wenxuan; Du, jianguo (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Battery Swapping Stations (BSSs) encountered several problems, such as an insufficient quantity and high construction costs, which restricted the development of the Battery Swapping Mode (BSM). This paper addresses these issues by examining government subsidies for the construction of BSSs and establishing a battery-swapping supply chain comprising the vehicle manufacturer, the battery-swapping operator, and the consumer. It employs a game model to investigate the impact of subsidy policies on the BSM, solving for the optimal battery-swapping electric vehicle selling price, battery rental price, comprehensive construction level of BSS, and government subsidy proportion. The study simulates the game equilibrium using real-world battery-swapping market data and analyzes the enhancement brought by government subsidies on the BSM. The findings reveal that: (1) The effect of government subsidies does not consistently improve with an increase in the subsidy proportion. Based on changes in social welfare, there exists a reasonable range for government subsidies, with the highest social welfare observed at a subsidy proportion of approximately 85%. (2) Sensible government subsidies for the construction of BSSs effectively boost their numbers, expand market demand, increase social welfare, elevate construction standards, and enhance manufacturer and operator profits. (3) For the battery-swapping operator, the impact of a balanced battery ratio on profits far outweighs the subsidy proportion. Furthermore, a higher battery ratio is not conducive to the long-term sustainability of the BSM.